2020
DOI: 10.31849/utamax.v2i2.3067
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Students’ Knowledge on a Novel Learning Strategy: What is Interesting about Blended Learning for EFL University Students?

Abstract: This research aimed at exploring students’ interest and knowledge in blended learning context at English Education Department in Universitas Lancang Kuning (Unilak). This descriptive quantitative research involved 27 out of 135 students as the samples as they are part of a class that uses blended learning actively through their entire semester. These 27 students were selected by using random sampling technique from fourth, sixth, and eight semester in regular class. The questionnaire used as the main instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Survey research collects information from a sample of individuals through their responses to questions (Yuliana et al, 2020). This survey was designed as a descriptive quantitative study in nature and sought an answer to the research questions.…”
Section: Designmentioning
confidence: 99%
“…Survey research collects information from a sample of individuals through their responses to questions (Yuliana et al, 2020). This survey was designed as a descriptive quantitative study in nature and sought an answer to the research questions.…”
Section: Designmentioning
confidence: 99%
“…The twenty-first century is a new era with new student challenges and responsibilities. A new way of teaching English has come about with the introduction of technology into our lives (Yuliana, 2020). One of the essential skills that students must be mastered for further study nowadays is reading skills as they are demanded to read a lot in their study program.…”
Section: Introductionmentioning
confidence: 99%
“…There are several strategies that can be applied, such as TPR (total physical response, songs, music and movement, and stories. Research (Yuliana et al, 2020) shows that blended learning implemented for two years has a high level of interest and knowledge among students in the Department of English Education. In similar research by (El Gendy, 2022), the results showed the effectiveness of a program based on several fun learning strategies to develop learning motivation and several intelligence skills that worked as input to reduce attention deficit disorder and hyperactivity in kindergarten children.…”
Section: Introductionmentioning
confidence: 99%